Multifidus muscle retracted and preserved in resection of malignant bone tumor in the sacral ala. Issue 10 (12th October 2021) - Sakamoto, Akio; Otsuki, Bungo; Noguchi, Takashi; Matsuda, Shuichi
Abstract: Resection of malignant tumors in the posterior pelvis requires multidirectional approaches for the resection and the subsequent spine-pelvic fixation. The multifidus muscle can be scarified during the operation. This is a case report of a 44-year-old male with a secondary chondrosarcoma arising from an osteochondroma in the sacral ala. Recurrence occurred 11 months after the initial operation, and the resected tissue from the recurrence was diagnosed as a chondrosarcoma. In both operations, the multifidus muscle was elevated from its distal attachment to provide an adequate view of the tumor resection and insertion of spine-pelvic instrumentation. An adequate view by elevation of the multifidus muscle is useful for a safe operation. A preserved multifidus muscle covering the instrumentation may reduce the risk of infection. The elevation and preservation of the multifidus muscle is an easy and simple method that contributes to successful resection of a malignant tumor of the pelvis.